Oligodendroglia and Myelin in Neurodegenerative Diseases: More Than Just Bystanders? - Ettle, Benjamin; Schlachetzki, Johannes; Winkler, Jürgen (Molecular Neurobiology, 2016)
Oligodendrocytes, the myelinating cells of the central nervous system, mediate rapid action potential conduction and provide trophic support for axonal as well as neuronal maintenance. Their progenitor cell population is widely distributed in the adult brain and represents a permanent cellular reservoir for oligodendrocyte replacement and myelin plasticity. The recognition of oligodendrocytes, their progeny, and myelin as contributing factors for the pathogenesis and the progression of neurodegenerative disease has recently evolved shaping our understanding of these disorders. In the present review, we aim to highlight studies on oligodendrocytes and their progenitors in neurodegenerative diseases. We dissect oligodendroglial biology and illustrate evolutionary aspects in regard to their importance for neuronal functionality and maintenance of neuronal circuitries. After covering recent studies on oligodendroglia in different neurodegenerative diseases mainly in view of their function as myelinating cells, we focus on the alpha-synucleinopathy multiple system atrophy, a prototypical disorder with a well-defined oligodendroglial pathology.
EVALuna2:25347